Large-scale ruthenium- and enzyme-catalyzed dynamic kinetic resolution of (rac)-1-phenylethanol - Bogár, Krisztián; Martín-Matute, Belén; Bäckvall, Jan-E. (Beilstein Journal of Organic Chemistry, 2007)
The scale-up of the ruthenium- and enzyme-catalyzed dynamic kinetic resolution (DKR) of (rac)-1-phenylethanol (2) is addressed. The immobilized lipase Candida antarctica lipase B (CALB) was employed for the resolution, which shows high enantioselectivity in the transesterification. The ruthenium catalyst used, (η 5-C5Ph5)RuCl(CO)2 1, was shown to possess very high reactivity in the "in situ" redox racemization of 1-phenylethanol (2) in the presence of the immobilized enzyme, and could be used in 0.05 mol% with high efficiency. Commercially available isopropenyl acetate was employed as acylating agent in the lipase-catalyzed transesterifications, which makes the purification of the product very easy. In a successful large-scale DKR of 2, with 0.05 mol% of 1, (R)-1-phenylethanol acetate (3) was obtained in 159 g (97% yield) in excellent enantiomeric excess (99.8% ee).